The Crotalaria juncea metal transporter CjNRAMP1 has a high Fe uptake activity, even in an environment with high Cd contamination. Issue 14 (6th December 2018) - Nakanishi-Masuno, Tsugumi; Shitan, Nobukazu; Sugiyama, Akifumi; Takanashi, Kojiro; Inaba, Shoko; Kaneko, Shuji; Yazaki, Kazufumi
Abstract: Large quantities of Fe and Cd accumulate in the leaves of the metal-accumulating leguminous plant, Crotalaria juncea . A member of the metal transporter NRAMP family was cloned from C. juncea . The amino acid sequence of this clone, designated CjNRAMP1, was similar to the sequence of Arabidopsis AtNRAMP1, which is involved in Fe and Cd transport. Organ-specific analysis showed that CjNRAMP1 mRNA was expressed mainly in the leaves of C. juncea plants, as well as in stems and roots. Use of green fluorescent protein fused to CjNRAMP1 suggested its localization to the plasma membranes of plant cells. Complementation experiments using yeast strains with impaired metal transport systems showed that CjNRAMP1 transported both Fe and Cd in an inward direction within the cells. Transgenic Arabidopsis plants overexpressing CjNRAMP1 showed high tolerance to Cd, with Cd translocation from roots to leaves being substantially greater in transgenic than in wild-type plants. Overexpression of CjNRAMP1 resulted in a greater accumulation of Fe in shoots and roots, suggesting that CjNRAMP1 recognizes Fe and Cd as substrates and that the high Cd tolerance of CjNRAMP1 is due to its strong Fe uptake activity, even in the presence of high Cd concentrations in the rhizosphere.